ANALYSIS OF SURFACE RUNOFF DISCHARGE OF PONGKERU WATERSHED AT LEDU-LEDU DAM AND CLEAN WATER PIPE NETWORK - Franita Leonard; Hasanuddin; Wahyuni (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Surface runoff is one of the important hydrological components to understand, especially in the context of land use planning and drainage systems. This study aims to analyze the amount of surface runoff discharge that occurs in the Pongkeru River Basin (DAS) using the rational method. The calculation results show that the runoff discharge in the Pongkeru DAS reaches 5.31 m³/second. Changes in land use and reduced infiltration areas play a major role in increasing runoff discharge. Therefore, integrated watershed management and environmentally friendly land use planning are essential as a basis for making the right decisions in sustainable environmental and water resource management.